Plastic People of the Universe - Chytilova, Jana (Czech Television, 2001)
Soros Documentary Fund Formed in 1968, following the Soviet invasion of Czechoslovakia, the rock band, Plastic People of the Universe (PPU) was inspired by American music banned by the Communist regime, including The Velvet Underground, Frank Zappa, Captain Beefheart, and The Doors. During the 1970s and early 1980s, the Czechoslovakian government banned PPU from performing which resulted with PPU conducting a series of clandestine engagements in defiance of the government restrictions. The documentary traces the different stages in the band's history that spans over more than 30 years and is tightly connected with the political developments in the country and offers a chronological look at the history of the band, featuring unique archive footage, photographs, musical excerpts, period press material and interviews of the musicians and their friends, including Václav Havel and Lou Reed.